2022
DOI: 10.1093/nsr/nwac104
|View full text |Cite
|
Sign up to set email alerts
|

A CRISPR/Cas12a-empowered surface plasmon resonance platform for rapid and specific diagnosis of the Omicron variant of SARS-CoV-2

Abstract: The outbreak of the COVID-19 pandemic is partially due to the challenge of identifying asymptomatic and pre-symptomatic carriers of the virus, and thus highlights a strong motivation for diagnostics that can be rapidly deployed with high sensitivity. On the other hand, several concerned SARS-CoV-2 variants, including the Omicron, are required to be identified as soon as the samples are identified as ‘positive’. Unfortunately, a traditional PCR test does not allow their specific identification. Herein, for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(106 citation statements)
references
References 41 publications
0
73
0
Order By: Relevance
“…Magnetic resonance imaging (MRI), a technique with a superior spatial resolution and contrast, has been extensively applied in clinical diagnosis without using harmful high-energy radiation. 1–5 The physical principles of MRI rely on the amount of water molecules in the examined area and finally the measurements show the spatial distribution of the relaxation of water protons. 6 Hence, effective MRI contrast agents must accelerate proton relaxation processes to shorten the T 1 (spin–lattice)/ T 2 (spin–spin) relaxation time and result in brighter/darker signals of the target tissues than the background.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI), a technique with a superior spatial resolution and contrast, has been extensively applied in clinical diagnosis without using harmful high-energy radiation. 1–5 The physical principles of MRI rely on the amount of water molecules in the examined area and finally the measurements show the spatial distribution of the relaxation of water protons. 6 Hence, effective MRI contrast agents must accelerate proton relaxation processes to shorten the T 1 (spin–lattice)/ T 2 (spin–spin) relaxation time and result in brighter/darker signals of the target tissues than the background.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Xue et al reported a bismuthene-enabled fluorescence quenching biosensor to detect microRNA, which is relevant to the fields of biosensors and medicine [ 18 ]. In 2022, Chen et al demonstrated a methodology of photonic clustered regularly interspaced short palindromic repeat (CRISPR) sensing for rapid and specific diagnosis of the Omicron variant of SARS-CoV-2 [ 19 ]. This innovative CRISPR-empowered surface plasmon resonance platform will further contribute to the field of biomedical sensors.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with the results of the DNA sequencing, this assay achieved 83.3–100% positive prediction and 85.7–100% negative prediction. The approach of selecting mutations located in the PAM-proximal region has also been exploited to develop other assays for the differentiation and detection of SARS-CoV-2 and its variants [ 102 , [137] , [138] , [139] , [140] ]. In these assays, CRISPR-Cas12a-mediated detection was incorporated with other isothermal amplification techniques such as recombinase polymerase amplification (RPA), loop-mediated isothermal amplification (LAMP) and with various detection methods such as the surface plasmon resonance (SPR) and LED light-based visual/cellphone detection [ 102 , [137] , [138] , [139] , [140] ].…”
Section: Crispr-cas12-based Methods For the Detection Of Variantsmentioning
confidence: 99%